2014
DOI: 10.1108/mf-10-2013-0305
|View full text |Cite
|
Sign up to set email alerts
|

Doing good with or without being known? Media coverage of corporate social performance and its impact on corporate financial performance

Abstract: Purpose – The purpose of this paper is to examine the media coverage of corporate social performance (CSP), as well as the ultimate impact that such coverage has on the financial performance of corporate entities. Design/methodology/approach – Based on a sample of financial holding companies (FHC) listed on the Taiwan Stock Exchange, the authors select the two most popular newspapers in Taiwan, to construct the unique media coverage of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Rupley et al (2012) found no significant relation between positive or neutral media tone and environmental disclosure, yet found that negative media coverage significantly drives firms' managers towards environmental disclosure. Chih and Chih (2014) found a positive association between positive media tone and stock returns, while neutral and negative media coverage were not significant. We argue that to convince stakeholders that their strategic plans can overcome negative publicity; firms provide higher levels of SD when facing negative media.…”
Section: Media ''Tone''mentioning
confidence: 84%
See 2 more Smart Citations
“…Rupley et al (2012) found no significant relation between positive or neutral media tone and environmental disclosure, yet found that negative media coverage significantly drives firms' managers towards environmental disclosure. Chih and Chih (2014) found a positive association between positive media tone and stock returns, while neutral and negative media coverage were not significant. We argue that to convince stakeholders that their strategic plans can overcome negative publicity; firms provide higher levels of SD when facing negative media.…”
Section: Media ''Tone''mentioning
confidence: 84%
“…Post-regression estimation tests reveal that the fixed effect model is a possible fit to our data set (Yekini et al, 2017). Based on prior studies of media coverage, media tone and firm-specific variables (García-Sá nchez et al, 2011; Rupley et al, 2012;Garcia-Sanchez et al, 2014;Chih and Chih, 2014;Cahan, et al, 2015;Aly et al, 2018;Byun and Oh, 2018;Zaman et al, 2018), we investigate whether media coverage (volume), media tone (positive, neutral and negative) and the interaction between media tone and INEDs affect the level of SD by UAE listed non-financial firms.…”
Section: Strategic Information Disclosure Index (Dependent Variable)mentioning
confidence: 92%
See 1 more Smart Citation
“…If so, then findings of superior performance are the result of an additional fifth factor beyond the Carhart four factor model. For instance, Chih and Chih (2014) found that only information on positive CSR activities provided by the media lead to a favorable reaction by shareholders. In addition, not all positive CSR news was 'good news': positive employee welfare news, in particular, can result in negative performance, perhaps indicating that shareholders see such a use of firm resources will ultimately be detrimental to maximizing shareholder value.…”
Section: Corporate Social Responsibility (Csr) and Firm Valuementioning
confidence: 99%
“…Linking CSR activities directly to firm value can be difficult. Not only does the information on such activities need to be credible, but enough shareholders need to be interested in and approve of CSR behavior to link CSR rankings to firm performance (Chih and Chih, 2014). It is also important to know whether a firm's superior performance is a compensation for additional risk; that is, if an informed investor perceives SR investments as riskier than others.…”
Section: Csr and Firm Valuementioning
confidence: 99%